2022
DOI: 10.3390/d14060426
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Vessel Transit on Vocalizations of the Taiwanese Humpback Dolphin

Abstract: Recent offshore windfarm development has led to increased vessel traffic in the Eastern Taiwan Strait, which is part of the habitat of the critically endangered Taiwanese humpback dolphin (Sousa chinensis taiwanensis). However, data on possible effects on the behavior of this endemic subspecies are lacking to date. In this study, we observed Taiwanese humpback dolphins’ acoustic behavior associated with shipping noise and analyzed their whistles and clicks before, during, and after vessel transit. Before vesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 53 publications
0
5
1
Order By: Relevance
“…Our results show that different to previous works 9 11 , 13 , 14 that observed differences in the whistle rate when vessels are present, we did not observe such a linear relation in our dataset, and that there is overlap in distributions for the ’with’ and ’without’ vessel cases for each of the whistle features. While one possible explanation is that our results are specific for the four explored dolphins, the differences could also be explained by the high number of whistles and vessels explored, which may capture more complexities within the dataset.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results show that different to previous works 9 11 , 13 , 14 that observed differences in the whistle rate when vessels are present, we did not observe such a linear relation in our dataset, and that there is overlap in distributions for the ’with’ and ’without’ vessel cases for each of the whistle features. While one possible explanation is that our results are specific for the four explored dolphins, the differences could also be explained by the high number of whistles and vessels explored, which may capture more complexities within the dataset.…”
Section: Discussioncontrasting
confidence: 99%
“…Here, we review the main methodologies. One recent work analysed the differences in the dolphins’ whistles emission rate and signal duration in the presence of vessel transit routes 9 . Roughly 1800 whistles were compared before, during, and after transit occurrences, and average differences were observed during and immediately after the passing of nearby vessels.…”
Section: Introductionmentioning
confidence: 99%
“…The busy vessel traffic in the Lingding waterway may further result in potential impacts on marine mammals including hearing masking and physiological damage to the auditory system (temporary threshold shift: TTS; permanent threshold shift: PTS), thereby shortening the communication distance of marine mammals (Merchant et al, 2014;Liu et al, 2017;Marley et al, 2017). When ships were presented, dolphins reduced vocalization behavior and emitted shorter calls in shorter frequency patterns, including whistles and echolocation signals (Hu et al, 2022). Hectic vessel traffic in the waters west of Hong Kong also interfered with the behavior and hearing of humpback dolphins (Sims et al, 2012).…”
Section: Underwater Noisementioning
confidence: 99%
“…Because of this dolphin population's high site fidelity, the bay has become a hotspot for dolphin-watching activities occurring throughout the year, with boats arriving every day primarily between 9 a.m. to 12 p.m. (noon), but also in the afternoons depending on the season (Perez-Ortega et al, 2021). The boats used for this purpose are small (typically 10 m in length) and are fitted with one or two engines that can range between 50 and 110 hp (Hu et al, 2022).…”
Section: Study Sitementioning
confidence: 99%
“…Both baleen and toothed whales respond acoustically to boat noise exposure by adjusting signal emission rate (Guerra et al, 2014). Bottlenose dolphins (Luis et al, 2014), humpback dolphins (Hu et al, 2022), and right whales (Parks et al, 2007a) are reported to decrease mean call rates in the presence of vessels. Changes in signal amplitude and frequency are also reported in various cetacean species.…”
Section: Introductionmentioning
confidence: 99%